Monitoring of multiresistant community-associated MRSA strains from patients with pathological processes of different localization - T. V. Sklyar; K. V. Lavrentievа; V. G. Gavrilyuk; N. V. Kurahina; M. O. Vereshchaha; O. A. Lykholat (Regulatory Mechanisms in Biosystems, 2018)
The therapy of infections, caused by methicillin-resistant Staphylococcus aureus (MRSA) with multiple resistance to antibiotics remains one of the most acute problems all over the world. It is all the more complicated since a priori the MSRA strains are not sensitive to the group of β-lactam antibiotics and multiresistant isolates are resistant to other groups of antimicrobial preparations, including antibiotics of choice (rifampicin, vancomycin, fusidic acid, co-trimoxazole and linezolid). From the samples of biomaterials of patients with pathological processes of different localization, we isolated 335 strains of bacteria, which were identified as Staphylococcus aureus, 169 (50.4%) of which were methicillin-resistant variants: 57.5% cultures were isolated from the nasal discharge; 50.7% – from faeces at intestinal dysbioses; by 40.0% – from conjunctival discharge, pharyngeal swab, outer ear swab and sputum; 33.3% – from urine samples. Antibiotic susceptibility of the isolated cultures was estimated by the disc-diffusion method and the method of serial dilution. The MRSA strains appeared to be most resistant to gentamycin, erythromycin (by 59.5% of cultures) and ciprofloxacin (53.3% of isolates), most sensitive – to vancomycin, co-trimoxazole and fusidic acid. The frequency of isolation of the cultures that are resistant to antibiotics did not exceed 4.1%. Rifampicin suppressed the growth of 75.8% and linezolid – of 100.0% of strains. Depending on the kind of biomaterial taken, MRSA strains, isolated from the nasal cavity, outer ear, urine samples, samples of sputum and faeces at intestinal dysbioses proved to be most resistant to the tested antimicrobial preparations. Rifampicin- and vancomycin-resistant strains of methicillin-resistant staphylococci made up 21.3% of the total number of the detected MRSA. They were most often isolated from the clinical samples taken from the nasal cavity and faeces. When determining minimal inhibitory concentration (MIC) of rifampicin and vancomycin, which are antibiotics of choice for treatment of infections caused by multiresistant MRSA, it was found that for 55.5% of the MRSA strains isolated from faeces, MIC of rifampicin coincided with the threshold value for this antibiotic and for 44.5%, it exceeded the threshold value by 2 times (4 µg/ml). 22.2% of them were characterized by the critical value of susceptibility to vancomycin (MIC ≥ 2 µg/ml). From rifampicin- and vancomycin-resistant MRSA stains, isolated from the nasal cavity, MIC of rifampicin coincided with the threshold value for this antibiotic for 66.7% of cultures, and exceeded it at least by 2 times for 33.3%. 11.1% of them were characterized by the critical level of susceptibility to vancomycin (MIC ≥ 2 µg/ml) and by 3.7% of strains exceeded MIC by 2 and 4 times respectively (4 and 8 µg/ml).